2021
DOI: 10.32598/ptj.11.2.446.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Upper Limb Disability in Overhead Women Athletes of Handball, Volleyball, Softball, and Swimming

Abstract: Purpose: The shoulder joint is one of the most commonly injured joints in sports and may lead to disability, especially in the upper extremities of overhead players (handball, volleyball, softball, and swimming). Methods: This research is a causal-comparative study. After the approval of the Ethics Committee of the Medical University of Tehran, this study was conducted on 120 overhead athletes (Mean±SD height: 1.69±0.07 m, Mean±SD weight: 63.54±7.79 kg, Mean±SD age: 21.96±2.94 years, Mean±SD body mass index: 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Many studies addressing upper limb injuries and pain tend to concentrate on sports involving overhead movements or throwing, such as handball [17][18][19][20], tennis [21,22], volleyball [18,19,23], baseball [24,25], judo [20], boxing [26,27] or water polo [28,29]. However, these studies exhibit variations in their research methodologies and diagnostic tools.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies addressing upper limb injuries and pain tend to concentrate on sports involving overhead movements or throwing, such as handball [17][18][19][20], tennis [21,22], volleyball [18,19,23], baseball [24,25], judo [20], boxing [26,27] or water polo [28,29]. However, these studies exhibit variations in their research methodologies and diagnostic tools.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in volleyball modality, authors 19 verified that athletes with rotator cuff lesions presented higher general and specific functional disability when compared to athletes without lesions. A study 20 showed a greater functional disability of the upper limb in female athletes practicing volleyball, when compared to softball and swimming athletes, and they did not find a significant difference in handball athletes, considering the similarity of attack and throwing movements. A study 21 evaluated 15 volleyball athletes in the juvenile category, associating pain by the Visual Analog Scale (VAS) and by the Disabilities of the Arm, Shoulder and Hand Questionnaire (DASH), and identified low pain intensities and little functional limitation, with no significant difference in the general and specific functional performance related to the sport.…”
Section: Introductionmentioning
confidence: 89%